Approach for decontaminating large rooms by dry fogging - Buhl Sebastian; Stich Alexander; Bulitta Clemens (Current Directions in Biomedical Engineering)
Many factors can negatively affect the effectiveness of cleaning and disinfection measures. Due to this situation, the Technical University of Amberg-Weiden in cooperation with aquagroup AG investigated a dry fogging technology as an automated system for decontamination of limited volumes. Preliminary tests in smaller rooms had already shown positive results in this context. An upscaling of the method would therefore be of interest, as it could be used to decontaminate rooms that are difficult or very costly to reprocess due to their size or layout. In order to evaluate the use of this system in operating theaters or larger rooms, a test setup was established in an aquagroup AG painting hall. In addition, thereby the effectiveness of the method can be evaluated in unprepared and unsealed rooms with high ventilation. Our results show a maximum germ reduction of over 5.7 log levels on tiles and 5.2 log levels on plastic. If further studies confirm these initial positive results, the dry fogging we are investigating could be another option for cleaning or disinfecting large areas quickly and effectively.